In vivo clinical trial of porous starch-hydroxyapatite composite biomaterials for bone regeneration - Sittiporn Punyanitya (2018)
© 2017 Trans Tech Publications, Switzerland. Biodegradable scaffold is an accepted and commercialized medical alternative choice for bone regeneration. In this project, we used our new invention, porous starch-Hydroxyapatite (HA) composite for in vivo clinical trial. The products were prepared from medical grade Thai rice starch mixed with high purity ( > 97%) HA powder from fresh cow bone, and already passed in vivo animal biocompatibility test, then processed by freeze-drying. There were 44 volunteers from orthopedic and neurosurgical division, 4 and 40 patients, respectively. The results were assessed by operative surgeons and nurses, pre-and intraoperative period, including size appropriateness, comfort handle, ease of cutting, void space filling, water stability, product weight, shelf storage, package opening, contamination risk and waste removal. All average satisfactory scales were more than 95% rating. For postoperative period, at least 6 months, the soft tissue swellings around surgical areas were resoluted about 3 days as usual healing process. There were no any symptoms or signs of infection or allergic reactions. The follow up of x-ray imaging showed well ossification about 2 months. All patients have gained good functional performance. So porous starch-HA composites biomaterial can be used for human bone and skull regeneration with completely safety and efficacy.